Mengungkap Tema Ritual Puah Manus Masyarakat As Manlea dan Implikasinya Terhadap Ketahanan Bangsa - Un Bria, Florens Maxi; Masan, Valentinus Kopong; Abatan, Yofince; Bustan, Fransiskus (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to reveal the views of the As Manlea community in Malaka Regency regarding the puah manus ritual. We involved six informants and analysed the results using qualitative methods with reflective thematic analysis techniques to reveal specific themes in the puah manus ritual. The study findings indicate that, for the As Manlea community, the puah manus ritual reflects: (1) the belief that betel nut enhances focus and concentration in performing tasks, (2) betel nut as the primary component in traditional prayer rituals, and (3) as an expression of inter-community communication. This study has significant implications for the forms of communication developing within local Indonesian communities. This study also serves as a foundation for fostering family ties, togetherness, and collaborative cooperation that bring harmony and increase participation in building families, communities, and the nation, especially in the Indonesia-Timor Leste border region.